Sṅags maṅ źib ʼjug : sṅags paʼi śes rig dus deb = Ngakmang research (Sṅags maṅ źib ʼjug rtsom sgrig khaṅ, 2002)
Journal on Tibetan Tantric research study of Rdzogs-chen Rñiṅ-ma-pa doctrines and rituals.